Croatia’s EU Accession : Case Studies on Reform and the Transposition of the Community Acquis - World Bank Group (World Bank, Vienna, 2018)
Croatia, a founding member of the former Republic of Yugoslavia and a current member of the European Union (EU), is a high-income country in Europe and Central Asia. Given that high quality financial reporting promotes good corporate governance, reduces uncertainty and risk, can help to lower the cost of capital, and boosts investor confidence, it will play a critical role in the country’s strategy to champion private sector led growth for economic development. Croatia’s preparation to join the EU required reform of its corporate financial reporting framework and practices, among other things, and laid the foundation for enhanced financial reporting and increased transparency. Although the country’s accession to the EU on July 1, 2013 was a single historical point in time, it encapsulated years of transformation of the statutory and institutional framework in every aspect of the economic, social, and political spheres of the country. The purpose of this report, which focuses on Croatia’s adoption and implementation of the corporate financial reporting aspects of the acquis’, company law, is to enhance understanding of how successful transitions work in practice, that is, what makes some reforms succeed where others fail. It attempts to answer questions such as: what happens when countries adopt international standards; what issues arise when one tries to merge differing legal traditions; how to achieve reform when there are capacity constraints and key implementing institutions are missing; what are the different strategies that can be used during various phases of a reform process; and, more generally, what factors encourage failure or lead to success?